2013
DOI: 10.1007/s10661-013-3415-9
|View full text |Cite
|
Sign up to set email alerts
|

Biomonitoring of cadmium, chromium, nickel and arsenic in general population living near mining and active industrial areas in Southern Tunisia

Abstract: The human health impact of the historic and current mining and industrial activities in Tunisia is not known. This study assessed the exposure to metals in the population of Southern Tunisia, using biomonitoring. The aim of this pilot study was to evaluate metal exposure on 350 participants living near mining and active industrial areas in the South of Tunisia. Blood specimens were analyzed for metals (Cd, Cr, As, and Ni) by Atomic Absorption Spectrometer equipped with Zeeman background correction and AS-800 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
3
5

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 91 publications
5
23
3
5
Order By: Relevance
“…Several studies reported that tobacco consumption constitutes an important source of chronic exposure to numerous xenobiotics, including heavy metals in particular Cd (IARC 1990;Wadhwa et al 2010;Viana et al 2011;Ashraf 2012). Previously, Cd and Ni exposure via tobacco consumption has been estimated based on the measurements of their concentrations in the blood of smokers compared to nonsmokers Gil et al 2011;Khlifi et al 2014b). Then, our results reflect that tobacco smoking and shisha could be major exposure sources to these toxic elements in both case and control groups.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Several studies reported that tobacco consumption constitutes an important source of chronic exposure to numerous xenobiotics, including heavy metals in particular Cd (IARC 1990;Wadhwa et al 2010;Viana et al 2011;Ashraf 2012). Previously, Cd and Ni exposure via tobacco consumption has been estimated based on the measurements of their concentrations in the blood of smokers compared to nonsmokers Gil et al 2011;Khlifi et al 2014b). Then, our results reflect that tobacco smoking and shisha could be major exposure sources to these toxic elements in both case and control groups.…”
Section: Discussionsupporting
confidence: 65%
“…Indeed, the Cd levels in blood samples of subjects occupationally exposed more than 14 years were eightfold greater than that of nonexposed (Table 4). The high metal levels in human blood have been reported in several previous investigations, which might be attributed to the occupational exposure source (Gil et al 2011;Hodnett et al 2012;Ivanenko et al 2012;Caciari et al 2012;Feki-Tounsi et al 2013a and2013b;Khlifi et al 2013;Khlifi et al 2014a and2014b;Ojo et al 2014;Choi and Kim 2014). Additionally, numerous epidemiological investigations suggested that exposure to toxic metals via occupational exposure has been evermore associated to nasal disease (Yang et al 2013;Sciskalska et al 2014) and sino-nasal cancer (Doll et al 1970;IARC 1990;Barbieri et al 2005;d'Errico et al 2009).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Reports from Spain and the Czech Republic also found significantly higher Cd blood levels in men (Lustigová and Puklová, 2006;Gil et al, 2011), whereas other studies did not find gender differences (CDC, 2005;Khlifi et al, 2014;Kuno et al, 2013) or revealed higher levels in females than males (Wennberg et al, 2006;Forte et al, 2011;Huang et al, 2013). Because men are more likely to smoke and to be occupationally exposed to metals, these divergent findings may be explained by the different composition of the study populations, which include occupational exposed individuals, people from the general population, smokers and non-smokers, or only non-smokers.…”
Section: Cadmiummentioning
confidence: 93%
“…For instance, the P95 of Cd was 2.31 lg L À1 in adults living in an industrial area in Tunisia (Khlifi et al, 2014). Mean Cd blood level was 24.10 lg L À1 in Chinese people residing in a polluted area (Wang et al, 2011); 9.81 lg L À1 in adults living in the vicinity of a cement factory in Pakistan (Afridi et al, 2011a); and 1.70 lg L À1 in Korean residents near municipal waste incinerators (Lee et al, 2012).…”
Section: Cadmiummentioning
confidence: 99%